Modelling and monitoring of stand volume, above ground biomass and carbon stocks of oil palm (Elaeis guineensis) plantations using landsat thematic mapper in Malaysia / Nazlin Asari - Asari, Nazlin (Institute of Graduate Studies, 2017)
Oil palm (Elaeis guineensis) plantations play important roles in the economics and sources of income to Malaysia. Accurate and reliable information on forecasts of resource availability and contribution of oil palm plantations on global carbon cycle are needed for its management efforts and planning. The need for effective inventories and monitoring methods has prompted this research into supplementing the ground field survey with the information from satellite remote sensing for developing methods for oil palm plantation inventory. For monitoring purposes, the effective procedures were developed using three dates of Landsat Thematic Mapper (TM) imagery. Field-measured above ground biomass (AGB), stand volume and carbon stocks values from 230.8 ha of oil palm plantations were compared with individual Landsat TM bands and nine vegetation indices. The potential models selected were obtained using stepwise and backward elimination method where R2, adjusted R2, Standard Error of Estimate (SEE), Root Mean Squared Error (RMSE) and Cp were examined in model development and validation